Management Modalities and Outcomes Following Acute Scaphoid Fractures in Children: A Quantitative Review and Meta-Analysis. (May 2019) - Shaterian, Ashkaun; Santos, Pauline Joy F.; Lee, Christine J.; Evans, Gregory R. D.; Leis, Amber
Background: Early evaluation and appropriate management of pediatric scaphoid fractures are necessary to avoid complications. To date, current management of pediatric fractures varies among providers. The objective of this study was to compare clinical outcomes following different treatment modalities.Methods: A PubMed literature search identified studies involving acute scaphoid fractures in children. Studies were evaluated for treatment provided and their respective effects on union rate, wrist range of motion, and wrist pain. Data were pooled across studies, and quantitative statistical analysis was conducted to compare outcomes.Results: Seventeen studies representing 812 acute pediatric scaphoid fractures were included in the current analysis. We found 93.5% of scaphoid fractures were treated with cast immobilization vs 6.5% treated surgically as 13 of 17 authors treated all fractures with immobilization vs 4 of 17 studies who offered surgical intervention. We found pediatric scaphoid fractures had excellent bone union rates (96.2%) with no difference between the cast immobilization and surgery groups ( P value NS). Long- and short-arm thumb spica immobilization protocols were commonly employed; however, we found no difference in the rates of union ( P value NS). At follow-up, 99.0% of patients treated nonoperatively had normal wrist range of motion and 96.8% were pain free.Conclusions: Pediatric scaphoid fractures have excellent outcomes. Nonoperative treatment results in a high rate of union with few posttreatment wrist symptoms. Nonsurgical treatment represents an adequate treatment modality in a majority of acute pediatric scaphoid fractures, wherein the role for surgery needs to be better defined.